CLINICAL, CULTURAL, ENDOCRINE AND THERAPEUTIC EVALUATION OF POSTPARTUM METRITIS IN SURTI BUFFALOES - PATIL, R D; PATEL, J A; DHAMI, A J; SARVAIYA, N P (The Indian Journal of Animal Reproduction, 2023)
This study was carried out on 40 postpartum metritic Surti buffaloes divided into five groups each of eight animals. The study included use of four treatment lines and one control group, viz., Group I- Metronidazole (500 mg) I/U for 5 days; Group 11-Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) I/U for 5 days; Group Ill- Ciprofloxacin (1500 mg) and Tinidazole (1800 mg) I/U for5 days plus PGF20 25 mg i/m once on first day; Group IV-Ceftiofur(long acting) @ 6.6 mg/kg body wt subcutaneously once and Group V (control)- Normal saline I/U for 5 days. The response to these therapeutic regimes was evaluated by comparing the clinical, cultural and endocrine changes before and after 5 days of treatment. The mean rectal temperature recorded after treatment was significantly (P<0.01) lower than the pre-treatment value in all four treatment groups. No significant change was however observed in control group. The mean values of plasma estradiol concentration were significantly (P<0.01) higher and progesterone values lower (P<0.01) on day 6 post-treatment than the corresponding pre-treatment values in all five groups. Microbial examination of uterine discharge revealed that 38 (95.00 %) animals were positive for micro-organisms and 2 (5.00 %) were sterile. Of the 38 samples, 31 (81.58%) had single and 7 (18.42%) had mixed bacterial isolates. Gram-ve bacilli were the predominant organisms (64.52 %) in metritic buffaloes. The therapeutic response achieved by various drugs and combination of drugs assessed by clinical recovery rate of the condition on 6th day post-treatment revealed that postpartum metritic buffaloes under groups I to V had a clinical cure rate of 50.00, 62.50, 87.50, 100.00 and 00.00 per cent, respectively. Clinically, Ceftiofur (long acting) was found to be the most effective drug followed by a combination of other antibiotics plus prostaglandin F20 and antibiotics alone.